Minimal and Maximal Sets uses. - Raad Aziz Hussain Al-Abdulla, Raghad Adnan Shanshool (Mathematical Statistician and Engineering Applications, 2023)
The aim of this paper is to introduce new types of sets maximal open set (M-open) and maximal closed set( M-closed) and minimal open set( m-open ) and minimal closed set( m-closed) with examples and theorems The relationships between them and other will be studied like M-compact ,M-compact sub space ,continuity function